Nursing Skills - Ernstmeyer, Kimberly; Christman, Elizabeth (Open textbook library., 2021)
This open access Nursing Skills textbook includes physical assessments routinely performed by entry-level registered nurses and basic nursing skills performed by licensed practical nurses. It is based on the Wisconsin Technical College System (WTCS) statewide nursing curriculum for the Nursing Skills course (543-102), the 2019 NCLEX-RN Test Plan, the 2020 NCLEX-PN Test Plan, and the Wisconsin Nurse Practice Act. Learning activities are included to encourage the student to engage in critical thinking and apply the nursing process while analyzing assessment findings.